Evaluation relationship between temporomandibular joint disorder and headache: A review literature - Farzaneh Aghahosseini; Nafiseh Sheykhbahaei (Tehran University of Medical Sciences, 2017)
Background and Aims: Headache is among the most common complaints in patients suffering from temporomandibular joint disorders (TMD). Thus, it seems that evaluation of patients with headache in terms of temporomandibular joint (TMJ) disorders is necessary. In people with TMD, parafunctional activities play an important etiologic role. Considering the high prevalence of bruxism and TMDs in patients with headache, assessment the accuracy and severity of this association can play a key role in diagnosis and treatment of these two phenomena. The purpose of this study was to investigate the relationship between bruxism, TMD and headache, also assessment the efficacy of TMD conservative therapy with a special approach to self-management in treating patients with headache. Materials and Methods: Motor searches of Cochrane, Medline and EMbase databases, PubMed, Google Scholar, Uptodate, BMJ clinical Evidence, MD consult and science direct by using of relevant key words were searched for article published between 2000 and 2015. A total of English language abstracts were reviewed, 80 full articles were obtained and among them, 30 relevant articles were reviewed in this study. Because of the high number of studies in this field, we divided the data into four group, bruxism and TMD, TMD and headache, bruxism, TMD and headache, treatment. Conclusion: Bruxism and temporomandibular disorders are the two main contributing factors in initiation and perpetuation of headache. Treatment of these two phenomena would be effective in the treatment of headache.